Difficulties in Comprehending Effective English Learning for Undergraduate Management Students - Rianita, Ni Made; Ratnadi, Ni Nyoman Ari (Journal of English Language and Education, 2025)
In Indonesia, English is a foreign language that is taught from elementary school to college. In practice, both teachers and students still face many difficulties during the learning process. Various responses can be found in class related to these difficulties, especially in student attitudes during the learning process, student learning outcomes, and participation in carrying out group activities. This study aims to describe the difficulties faced by undergraduate students of Management at Satya Dharma College of Economics in understanding English learning and the factors that cause them. This study uses a qualitative approach with questionnaires, observation, and documentation instruments. Data analysis was carried out in three ways, namely data reduction, data presentation, drawing conclusions and verification. The results of the study showed that the research subjects experienced various difficulties in learning English. This happened due to different levels of English language proficiency.